ประสิทธิผลของโปรแกรมส่งเสริมสมรรถนะแกนนํา ต่อการรับบริการตรวจมะเร็งปากมดลูก ตําบลเขาคราม อําเภอเมือง จังหวัดกระบี่ - เจริญสุข สมชาย (JOURNAL OF SOUTHERN TECHNOLOGY, 2015)
การวิจัยครั้งนี้เป็นการวิจัยกึ่งทดลองแบบกลุ่มเดียวก่อนทดลองและหลังการทดลอง มีวัตถุประสงค์ เปรียบเทียบสมรรถนะของแกนนําเกี่ยวกับ ความรู้เรื่องโรคมะเร็งปากมดลูก การตรวจคัดกรองมะเร็ง ปากมดลูกและการติดต่อสื่อสารเพื่อสร้างแรงจูงใจต่อการตรวจคัดกรองมะเร็งปากมดลูกก่อนและหลังได้รับ โปรแกรมส่งเสริมสมรรถนะและเพื่อศึกษาอัตราการเข้ารับการตรวจคัดกรองมะเร็งปากมดลูกของสตรีอายุ 30-60 ปี ตําบลเขาคราม อําเภอเมือง จังหวัดกระบี่ภายหลังการใช้โปรแกรมส่งเสริมสมรรถนะแกนนํา โดย โปรแกรมส่งเสริมสมรรถนะแกนนําประกอบด้วยการบรรยายประกอบสื่อและการสาธิตฝึกปฏิบัติการชักจูง กลุ่มเป้าหมาย กลุ่มตัวอย่าง ได้แก่ อาสาสมัครประจําหมู่บ้านที่พัฒนาขึ้นเป็นแกนนําในตําบลเขาคราม 6 หมู่บ้าน จํานวน 26 คน คัดเลือกกลุ่มตัวอย่างแบบเจาะจง ระยะเวลาของโปรแกรมจํานวน 2 วัน เครื่องมือ ที่ใช้ในการเก็บรวบรวมข้อมูลเป็นแบบสอบถามความรู้และแบบสังเกตทักษะการติดต่อสื่อสารที่ผ่านการ ตรวจสอบความเที่ยงตรง โดยผู้เชี่ยวชาญและทดลองใช้กับกลุ่มตัวอย่างในตําบลหนองทะเล อําเภอเมือง จังหวัดกระบี่ คํานวณจากสูตร KR-20 มีค่าความเชื่อมั่นเท่ากับ .82 เก็บข้อมูล 2 ครั้งคือก่อนทดลองและหลัง ทดลอง และนํามาวิเคราะห์สถิติบรรยายเป็นค่าความถี่ ค่าร้อยละ ค่าเฉลี่ย ค่าเบี่ยงเบนมาตรฐาน และ Paired Samples t-test ผลการวิจัยพบว่า หลังการทดลองแกนนํามีคะแนนเฉลี่ย ความรู้เรื่องโรคมะเร็งปากมดลูกในรายด้าน แตกต่างจากก่อนการทดลองอย่างมีนัยสําคัญทางสถิติที่ระดับ .05 หลังการใช้โปรแกรมส่งเสริมสมรรถนะ แกนนํา มีสตรีกลุ่มเป้าหมายมารับบริการตรวจมะเร็งปากมดลูกเพิ่มขึ้นจากร้อยละ 55.2 เป็นร้อยละ 61.3 แสดงให้เห็นว่าโปรแกรมส่งเสริมสมรรถนะแกนนํา สามารถนําไปใช้ในการเพิ่มอัตราการตรวจมะเร็งปากมดลูก ได้ และสามารถนําไปประยุกต์ใช้ในชุมชนอื่น ๆ ที่มีลักษณะประชากรและการให้บริการที่ใกล้เคียงกันต่อไป The Effectiveness of Competency Promoting Program for Leaders towards Cervical Cancer Screening, Khao Kram Sub-district, Mueang District, Krabi Province The aim of this quasi-experimental study was twofold: first, to explore the increasing knowledge and communication skills of the leaders who participated in competency promoting program for leaders towards cervical cancer screening in Khao Kram Sub-district, Mueang District, Krabi Province; second, to monitor and keep record on cervical cancer screening of the women, at the age of 30-60 years old living in Khao Kram Sub-district, who were under the supervision of the leaders participating in the program. Twenty six leaders purposively selected from all health volunteers of 6 villages in Khao Kram Sub-district (intervention group) received a 2-day competency promoting program. The program included several components, knowledge of cervical cancer, motivation, social support such as didactic instruction with visual aids and demonstrations. Outcomes were measured by knowledge questionnaires and communication skill observation at baseline (pre-intervention), and after the intervention. Content validity and reliability of the tools were performed (reliability =.82). In the data analysis; means, frequencies, percentages, standard deviations for description, and Paired Samples t-test were used for general information and knowledge. Findings, the intervention was associated with substantial and statistically significant improvements in scores of knowledge, benefits of pap smear, pap smear accessibility, and persuasion techniques for cervical cancer (p=0.005). After the program, there was an increase of the women who had pap smear test from 55.2 to 61.3 percent. These findings increase confidence that well designed interventions can be effective in increasing detection of cervical cancer case in Thailand and possibly elsewhere with similarly characteristics.